Mushroom refinement endeavor auspicate non green revolution in the offing - SHAUKET AHMED PALA; ABDUL HAMID WANI; ROUF HAMZA BODA; BILAL AHMAD WANI (Nusantara Bioscience, 2014)
Abstract. Pala SA, Wani AH, Boda RH, Wani BA. 2014. Mushroom refinement endeavor auspicate non green revolution in the offing. Nusantara Bioscience 6: 173-185. Mushroom can serve as food, tonic, and as medicine thus make people healthier, fitter and happier. They have a cracking potential for generating great socioeconomic impact in human welfare at local, national and international level. With the help of allied mushroom farming we can easily tackle the problem of food for growing world population; reduce environmental pollution by bioconversion of huge organic wastes into mushrooms; recycle huge quantity of organic wastes to mushroom crops, biofertilizers, and biogas; restore damaged environment by mushroom mycelia through mycoforestry, mycoremediation, mycofiltration and mycopesticides in a zero-emission fashion. They can be used to degrade radioactive industrial biocide wastes in an eco-friendly fashion. Since mushroom cultivation is an indoor agribusiness, it could have a great economic impact by generating employment, income and functional food requirements for rural people, especially in developing countries. How far mushroom cultivation can meet the functional food requirements; address the domestic food challenges, rising food prices and crisis vis a vis environmental sustainability will be thrust areas of this communication.